A dark‐tolerant diatom (Chaetoceros) cultured from the deep sea. Issue 2 (28th February 2022) - Mou, Shanli; Zhang, Zenghu; Zhao, Hanshuang; Nair, Shailesh; Li, Yuhang; Xu, Kuidong; Tian, Jiwei; Zhang, Yongyu
Abstract : Although the extreme conditions of the deep sea are typically not suitable for the growth of photosynthetic algae, accumulating evidence indicates that there are diverse healthy phytoplankton living in this environment. However, living phytoplankton from the deep sea have rarely been isolated and cultivated, and so our understanding of where they come from and how they adapt to (or tolerate) the extreme deep‐sea environment is limited. Here, under long‐term dark stress and subsequent light treatment, we successfully isolated a diatom from a depth of 1, 000 m in the Western Pacific Ocean. Morphological observations and molecular phylogenetic analysis revealed that it is affiliated to the genus Chaetoceros, and thus, we tentatively named it Chaetoceros sp. DS1. We observed that the chloroplast genome of this species, is most closely related to that of Chaetoceros simplex . It was shown to have a strong tolerance to darkness in that it maintained its morphological integrity and vitality for up to 3 months in complete darkness at room temperature. We also demonstrated that Chaetoceros sp. DS1 presented a facultative heterotrophic function. Its growth was promoted by many organic carbon sources (e.g., glycerine, ethanol, and sodium acetate) under low light conditions. However, under dark and high light conditions, the growth promotion effect of organic carbon was not obvious. Indeed, Chaetoceros sp. DS1 grew best under low light conditions, indicating that it likely came from the deeper layer of the euphotic zone. The facultative heterotrophic function of this diatom and tolerance to darkness may help it survive in these conditions or enter a dormant period in the deep sea.